Increased myofibrillar protein catabolism in Duchenne muscular dystrophy measured by 3-methylhistidine excretion in the urine. Issue 10 (October 1977) - McKeran, R O; Halliday, D; Purkiss, P
Abstract : Myofibrillar protein catabolic rate was calculated in seven patients with Duchenne muscular dystrophy from the amount of 3-methylhistidine excreted in the urine, and found to be over three times that found in a control series when expresses as the percentage of myofibrillar protein catabolised per day. It is suggested that measurement of myofibrillar protein catabolic rate may add a useful parameter in the study of muscle disorders.